2017
DOI: 10.1038/s41467-017-00221-3
|View full text |Cite
|
Sign up to set email alerts
|

ATR inhibition facilitates targeting of leukemia dependence on convergent nucleotide biosynthetic pathways

Abstract: Leukemia cells rely on two nucleotide biosynthetic pathways, de novo and salvage, to produce dNTPs for DNA replication. Here, using metabolomic, proteomic, and phosphoproteomic approaches, we show that inhibition of the replication stress sensing kinase ataxia telangiectasia and Rad3-related protein (ATR) reduces the output of both de novo and salvage pathways by regulating the activity of their respective rate-limiting enzymes, ribonucleotide reductase (RNR) and deoxycytidine kinase (dCK), via distinct molecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
77
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(80 citation statements)
references
References 70 publications
3
77
0
Order By: Relevance
“…While previous reports have linked ATR signaling to nucleotide metabolism through upregulation of RRM2 protein stability (Le et al, 2017), our model suggests that ATR also modulates nucleotide metabolism through increasing mTORC1 signaling (Fig. 3).…”
Section: Discussionmentioning
confidence: 64%
“…While previous reports have linked ATR signaling to nucleotide metabolism through upregulation of RRM2 protein stability (Le et al, 2017), our model suggests that ATR also modulates nucleotide metabolism through increasing mTORC1 signaling (Fig. 3).…”
Section: Discussionmentioning
confidence: 64%
“…Furthermore, dCK inactivation has also been associated with resistance to dG-mediated toxicity in PNP-deficient T-lymphoma cells 15 . We found that the lethality of PNP inhibitors be completely prevented by supplementing with a small molecule dCK inhibitor indicating that phosphorylation of dG by dGK does not contribute to the observed lethality at these timepoints ( Figure 2D) 4 .…”
Section: Samhd1-deficient Solid Tumor Models Are Sensitive To Pnp Inhmentioning
confidence: 90%
“…We found that SAMHD1 KO cells exhibited a 200-fold lower thymidine IC50 than SAMHD1 WT controls (Figure 5A). This selectivity was unique to thymidine and did not extend to other RNR inhibitors, including 3-AP, which function by preventing RNR tyrosyl radical regeneration 4 . Similar selectivity was observed using crystal violet proliferation analysis (Figure 5B).…”
Section: Samhd1 Prevents the Anti Proliferative Effects Of Thymidinementioning
confidence: 95%
See 2 more Smart Citations